Gambaran Kejadian Stunting Pada Balita Di Puskesmas Antang Kota Makassar - Riswandi; Fairus Prihatin Idris; Ella Andayanie (Window of Public Health Journal, 2025)
Stunting is a chronic nutritional problem caused by prolonged inadequate nutritional intake, generally due to food intake that does not meet nutritional needs. The government is working to address the problem of malnutrition and stunting. Improving nutrition and reducing the prevalence of stunting in children under two years old (baduta) from 32.9% in 2018 to 28% in 2019 is one of the national development priorities, as stated in the 2015-2019 national medium-term development plan. This study uses a descriptive analysis method with a quantitative approach. The results of this study show that of the 35 toddler respondents at the Antang Health Center in 2022, based on low birth weight in the Antang Health Center work area of ​​35 respondents, 14 toddlers had a birth weight of ≥2500 grams and 21 toddlers had a birth weight of <2500 grams, exclusive breastfeeding in the Antang Health Center work area of ​​35 respondents, 16 (45.7%) toddlers were given exclusive breastfeeding and 19 (54.3%) toddlers were not given exclusive breastfeeding, maternal nutritional knowledge at the Antang Health Center was good for 13 (37.1%), sufficient for 12 (34.3%) and less for 10 (28.6%). The economic status at Antang Health Center is ≥3,294,467, as many as 19 (54.3%) and <3,294,467, as many as 16 (45.7%), and the immunization history at Antang Health Center is as many as 35 toddlers with complete immunization status and as many as zero toddlers with incomplete immunization status. Based on the study's results, discussion, and conclusion, it is recommended that the Health Office and Health Center carry out more health promotion activities to prevent stunting in toddlers and mothers in the Antang Health Center work area.